The influence of pediatricians' recommendation on caregivers' COVID-19 vaccine acceptance for children: A nationwide cross-sectional survey study from USA - Mondal, Pritish; Sinharoy, Ankita (Frontiers in Pediatrics, 2023)
Background: The influence of pediatricians on parental acceptance of COVID-19 vaccine for children has not been well studied. We designed a survey to estimate the influence of pediatricians’ recommendations on caregivers’ vaccine acceptance while accounting for participants' socio-demographic and personal characteristics. The secondary objectives were to compare childhood vaccination rates among different age groups and categorize caregivers’ concerns. Overall, the study aimed to provide insight into potential pro-vaccination strategies that could integrate pediatricians and counter parental vaccine hesitancy. Methods: We conducted an online cross-sectional survey study using Redcap, in August 2022. We enquired COVID-19 vaccination status of family children (≥five years). The survey questionnaire included socio-demographic and personal characteristics: age, race, sex, education, financial status, residence, healthcare worker, COVID-19 vaccination status and side effects, children’s influenza vaccination status, and pediatricians’ recommendations (1-5 scale). Logistic regression and neural network models were used to estimate the influence of socio-demographic determinants on children’s vaccine status and build predictors’ ranking. Results: The participants (N=2622) were predominantly white, female, middle-class, and vaccinated against COVID-19 (89%). The logistic regression model was significant versus the null (likelihood-ratio χ2= 514.57, p<.001, pseudo-R2=.440). The neural network model also demonstrated strong prediction ability with a correct prediction of 82.9% and 81.9% for the training and testing models, respectively. Both models identified pediatricians’ recommendations, self-COVID-19 vaccination status, and post-vaccination side effects as dominant predictors of caregivers’ vaccine acceptance. Among the pediatricians, 70.48% discussed and had an affirmative opinion about COVID-19 vaccine for children. Vaccine acceptance was lower for children aged 5-8 years compared to older age groups (9-12 and 13-18 years), and acceptance varied significantly among the three cohorts of children (χ2= 65.62, p<0.001). About half of the participants were concerned about inadequate vaccine safety information availability for under-five children. Conclusions: Pediatricians’ affirmative recommendation was significantly associated with caregivers’ COVID-19 vaccine acceptance for children while accounting for participants’ socio-demographic characteristics. Notably, vaccine acceptance was lower among younger compared to older children, and caregivers’ uncertainty about vaccine safety for under-five children was prevalent. Thus, pro-vaccination strategies might incorporate pediatricians to alleviate parental concerns and optimize poor vaccination rates among under-five children.